Evaluating alternative energy carriers in ferry transportation using a stochastic multi-criteria decision analysis approach. (September 2020) - Aspen, Dina Margrethe; Sparrevik, Magnus
Highlights: A stochastic multi-criteria decision making model is applied to maritime transportation. The approach utilizes stochastic techniques to handle uncertain input values. A case study of a ferry crossing is used to demonstrate the approach. Abstract: As part of ship acquisition decision making, owners and key stakeholders need to evaluate ship design and technology solutions across economic and environmental criteria in addition to safety and other regulatory requirements. Changes in technology, market, fiscal and other regulatory conditions may furthermore significantly influence value retention over the investment period. Multi-criteria decision making (MCDM) provides structure and clarity in otherwise complex decision problems, allowing decision makers to identify promising courses of action in a holistic manner. Combined with stochastic evaluation techniques, MCDM may facilitate problem exploration and learning in situations where outcomes are uncertain. In this article, we combine two variants of "Stochastic Multicriteria Acceptability Analysis" (SMAA) with "Technique for Ordering of Preference by Similarity to Ideal Solution" (TOPSIS) to evaluate the use of biofuels, natural gas and electricity on Norwegian ferry crossings. We analyze uncertain criteria values for environmental impacts, costs, fuel access and public acceptance across seven ferry combinations for a crossing. Criteria weighting is performed deterministically and stochastically to extract and interpret the conditions under which alternatives perform well or poorly. The case study shows that all-electric propulsion is preferable, while plug-in hybrid solutions with natural gas also give a robust performance. The approach is beneficial in handling multiple, uncertain performance metrics and provides a transparent and holistic foundation for evaluating marine emission reduction technology options in ship acquisition decision contexts.